Intercultural Communications as a Tool of Formation of the Global Axiological System in the Conditions of Establishment of the Entrepreneurial Type of Thinking of the Russian Society - Shvachkina, Lyudmila A.; Rodionova, Valentina I. (Journal of History Culture and Art Research, 2018)
The article is devoted to the influence of intercultural communications on society in the conditions of establishment of the entrepreneurial type of thinking in Russia. The authors note standardization of entrepreneurial culture and increase of priority of global market’s values with bearers of the entrepreneurial type of thinking, who represent the most active and independent part of the Russian society – which stimulates socio-cultural contradictions in the modern society. The conclusion is made on intercultural communications in the conditions of establishment of the entrepreneurial type of thinking in Russia as a tool of formation of the global axiological system.